Relationship Between Bone Bruise Volume and Patient Outcomes After ACL Reconstruction. Issue 2 (23rd February 2023) - Galloway, Connor; Ward, Hallie; Higbie, Steven; Kleihege, Jacquelyn; Kumaravel, Manickam; Lowe, Walter R.; Bailey, Lane
Background: Subchondral bone injuries, or bone bruises, are commonly observed on magnetic resonance imaging (MRI) after anterior cruciate ligament (ACL) injury. The current relationship between bone bruise volume and postsurgical outcomes remains poorly understood. Purpose: To examine the influence of bone bruise volume on self-reported and objective functional outcomes at the time of return to play and 2 years following ACL reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: Clinical, surgical, and demographic data were obtained for a sample of convenience utilizing a single-surgeon ACL database (n = 1396). For 60 participants, femoral and tibial bone bruise volumes were estimated from preoperative MRI. Data obtained at the time of return to play included International Knee Documentation Committee (IKDC-2000) score, ACL–Return to Sport after Injury (ACL-RSI) score, and performance on an objective functional performance battery. Two-year follow-up data included graft reinjury rate, level of return to sport/activity, and self-reported knee function using the Single Assessment Numeric Evaluation (SANE). The forward stepwise linear regression was used to determine the relationship between bone bruise volume and patient function. Results: The distribution of bone bruise injuries was as follows: lateral femoral condyle (76.7%), lateral tibial plateau (88.3%), medial femoral condyle (21.7%), and medial tibial plateau (26.7%). Mean total bone bruise volume of all compartments was 7065.7 ± 6226.6 mm 3 . At the 2-year follow up, there were no significant associations between total bone bruise volume and time of return to play ( P = .832), IKDC-2000 score ( P = .200), ACL-RSI score ( P = .370), or SANE score ( P = .179). Conclusion: The lateral tibial plateau was the most frequent site to sustain bone bruise injury. Preoperative bone bruise volume was not associated with delayed time to return to sport or self-reported outcomes at time of return to play or at 2 years postoperatively. Registration: NCT03704376 (ClinicalTrials.gov identifier).